Proenvironmental behavior: Critical link between satisfaction and place attachment in Australia and Canada - Ramkissoon, Haywantee; Mavondo, F. (Cognizant Communication Corporation, 2017)
This study explores issues of scale equivalence and generalizability in national parks. Visitors' place satisfaction, proenvironmental behavior, and place attachment are measured across two qualitatively distinct populations in Australia and Canada. Techniques employed in this cross-country study bring an important contribution to tourism research. The primary focus is to establish measure equivalence before undertaking hypothesis testing using structural equation modeling on a sample of 339 repeat visitors at the Dandenong Ranges National Park, Australia, and 296 repeat visitors at the Bruce Peninsula National Park, Canada. Results from both samples indicate (a) there is measure equivalence between the Australian and Canadian samples allowing comparability of findings, (b) a positive and significant effect of visitor place satisfaction on proenvironmental behavioral intentions, (c) a significant and positive influence of proenvironmental behavioral intention on place attachment (place identity, place dependence, place social bonding, place affect), and (d) a significant and negative effect of visitor place satisfaction on place social bonding. The main finding relates to the promotion of proenvironmental behaviors among national park users that-in addition to individual benefits- provides environmental sustainability as well as practical benefits for park managers and society.